Antimicrobial peptides trigger a division block in Escherichia coli through stimulation of a signalling system - Srujana S. Yadavalli (Nature Portfolio, 2016)
The PhoQ/PhoP system regulates antimicrobial peptide defense in bacteria. Here the authors show that at sublethal concentrations of antimicrobial peptides, PhoPQ induces QueE, that then localizes to the divisome and blocks cell division independently of its function in queuosine biosynthesis.